Rapid and Accurate Identification of SARS-CoV-2 Variants Using Real Time PCR Assays - Borillo, Gwynngelle A.; Kagan, Ron M.; Marlowe, Elizabeth M. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Genomic surveillance efforts for SARS-CoV-2 are needed to understand the epidemiology of the COVID-19 pandemic. Viral variants may impact routine diagnostic testing, increase viral transmissibility, cause differences in disease severity, have decreased susceptibility to therapeutics, and/or confer the ability to evade host immunity. While viral whole-genome sequencing (WGS) has played a leading role in surveillance programs, many laboratories lack the expertise and resources for performing WGS. This study describes the performance of multiplexed real-time reverse transcription-PCR (RT-PCR) assays for identification of SARS-CoV-2 variants. Methods SARS-CoV-2 specimens were tested for spike-gene variants using a combination of allele-specific primer and allele-specific detection technology (PlexPrime® and PlexZyme®). Targeted detection of spike gene mutations by RT-PCR was compared to variant detection in positive specimens by WGS, including the recently emerged SARS-CoV-2 Omicron variant. Results A total of 398 SAR-CoV-2 RT-PCR positive and 39 negative specimens previously tested by WGS were re-tested by RT-PCR genotyping. PCR detection of spike gene mutations N501Y, E484K, and S982A correlated 100% with WGS for the 29 lineages represented, including Alpha (B.1.1.7), Beta (B.1.351), and Gamma (P.1). Incorporating the P681R spike gene mutation also allowed screening for the SARS-CoV-2 Delta variant (B.1.617.2 and AY sublineages). Further sampling of 664 specimens that were screened by WGS between June and August 2021 and then re-tested by RT-PCR showed strong agreement for Delta variant positivity: 34.5% for WGS vs 32.9% for RT-PCR in June; 100% vs 97.8% in August. In a blinded panel of 16 Omicron and 16 Delta specimens, results of RT-PCR were 100% concordant with WGS results. Conclusions These data demonstrate that multiplexed real-time RT-PCR genotyping has strong agreement with WGS and may provide additional SARS-CoV-2 variant screening capabilities when WGS is unavailable or cost-prohibitive. RT-PCR genotyping assays may also supplement existing sequencing efforts while providing rapid results at or near the time of diagnosis to help guide patient management.